Opportunities and Status of Wheat Row Planting in Smallholder Farmers in Elfeta District Oromia Regional State Ethiopia - Dajane Ajema Sima; Habtamu Fekadu Etefa (Turkish Journal of Agriculture: Food Science and Technology)
To enhance wheat yield, adoption and management practices have become a major concern of agricultural extension activities and low produce of wheat is partly due to poor agronomic practices in Ethiopia. Compared to broadcasting system, row planting gives better yield with quality of the seed at harvesting period. The study was conducted to assess the opportunities and status of wheat row planting by farmers. This study was used descriptive research design and employed both quantitative and qualitative approaches. Primary data were collected from 141_sample households which were selected randomly. Additional information was obtained from focus group discussion and key informant interview. The data has been analyzed by using simple descriptive statistics such as mean, percentage and standard deviation. Moreover, inferential statistics like chi-square and t-test were used. The result shows that, education level, family size, farmers experience, seeding rate per hectare, yield per hectare, fertilizer rate per hectare and income of household were positive association with wheat row planting in the study area. Also, non-adopter farmers was not use the existing opportunity such as off-farm income generating activities, contact with extension agents, credit use, membership in cooperatives and improved seed in the study area. Moreover, more than half of smallholders not adopt the wheat row planting system; meaning, still they use broadcasting system of Planting in their farms. Therefore, the study concludes that, Policies and strategies that focus on farmers’ education, implementation of well-established extension package are helpful so as to achieve wider adoption of row planting technology of smallholder farmer in the study area.